Smart grid security : innovative solutions for a modernized grid - Skopik, Florian; Smith, Paul (Syngress advanced topics in information security., 2015)
This book provides a holistic view of leading edge smart grid security research by providing a complete presentation of forward-looking research in all areas of smart grid security. It will enable practitioners to learn about upcoming trends, scientists to share new directions in research, and government and industry decision-makers to prepare for major strategic decisions regarding implementation of smart grid technology. It includes coverage of risk management, operational security, and secure development of the smart grid; and covers key technical topics, including threat types and attack vectors, threat case studies, smart metering, smart home, e- mobility, smart buildings, DERs, demand response management, distribution grid operators, transmission grid operators, virtual power plants, resilient architectures, communications protocols and encryption, as well as physical security. --